An ANALYSIS OF CONNOTATIVE MEANING IN ED SHEERAN’S SONG LYRICS - kamisah S.Pd M.Pd; Srimaharani Tanjung; Siti Nurhaliza Nasution (Jurnal TAROMBO, 2022)
The purpose of this study were to find out: 1) the kind of connotative meaning is found in Ed Sheeran’s 10 song lyrics, 2) the connotative meaning contained in the lyrics of Ed Sheeran’s song and 3) the most dominant types of connotative meaning in the 10 lyrics of Ed Sheeran’s song. In collecting the data, the researcher used documentation. By using connotative meaning theory of Hook’s in Cahyani. The researcher focused to analyze connotative meaning that include 2 types, namely: Positive connotation and negative connotation. The result of the study showed that from Ed Sheeran’s song lyrics, the researcher found there were 41 utterance containing the types of connotative meaning. Positive connotation with percentage 70.5% and Negative connotation 29.5%. Based on the result of the study, it can be concluded that the most dominant types of Connotative meaning in Ed Sheeran’s song lyrics is Positive connotation. While the meanings contained in the 10 lyrics of Ed Sheeran’s songs were: Disappointment and happiness.